Pengaruh Resiliensi Matematis terhadap Kemampuan Pemecahan Masalah Matematika Siswa MAS Miftahussalam Medan - M. Fauzan Zannurrain; Machrani Adi Putri Siregar; Ammamiarihta (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to determine the significant influence of mathematical resilience on students' mathematical problem-solving ability, as well as measure the magnitude of this influence. The approach used is quantitative with an ex post facto (comparative causal) design, where variables have occurred before the study was conducted. The research population included all grade XII students at MAS Miftahussalam Medan, with a sample of 33 students selected through simple random sampling techniques. The research instrument consisted of a questionnaire to measure mathematical resilience and a test to measure mathematical problem-solving ability. The validity and reliability of the instruments were tested through preliminary trials. Data analysis was carried out through a prerequisite test (normality and linearity), followed by a simple linear regression test, t-test, and determination coefficient. The results of the analysis showed a regression equation Y = 16.803 + 0.273X, with a value of t_hitung = 3.784 > t_tabel = 2.039 at a significance level of 5%, so that H₀ was rejected and H₁ was accepted. The determination coefficient of 0.316 showed that mathematical resilience contributed 31.6% to students' mathematical problem-solving ability, while 68.4% was influenced by other factors. These findings confirm the importance of strengthening mathematical resilience in an effort to improve students' problem-solving skills more effectively.